2019
DOI: 10.14423/smj.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Hospital Resources and Specialty Services for Stroke Care in North Carolina

Abstract: Objectives: Effective regionalization of acute stroke care requires assessment and coordination of limited hospital resources. We described the availability of stroke-specific hospital resources (neurology specialty physicians and neuro-intensive care unit [neuro-ICU] bed capacity) for North Carolina overall and by region and population density. We also assessed daily trends in hospital bed availability. Methods: This statewide descriptive study was conducted with data from the State Medical Asset Resource Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…A variety of studies have indicated options to shorten the time from stroke onset to reperfusion, such as cooperative method (9), workflows in hospitals (10,11), rapid diagnoses (12), and public awareness campaigns (13). However, infrastructure and human resources such as spatial accessibility (14)(15)(16), facilities (i.e., the number of beds, equipment), and human resources (17) are critical. Optimization of supply against demand is a crucial issue because the allocation of facilities and human resources affects the onset-to-reperfusion time in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have indicated options to shorten the time from stroke onset to reperfusion, such as cooperative method (9), workflows in hospitals (10,11), rapid diagnoses (12), and public awareness campaigns (13). However, infrastructure and human resources such as spatial accessibility (14)(15)(16), facilities (i.e., the number of beds, equipment), and human resources (17) are critical. Optimization of supply against demand is a crucial issue because the allocation of facilities and human resources affects the onset-to-reperfusion time in stroke.…”
Section: Introductionmentioning
confidence: 99%